Samoa : Assessment of the Supervision and Regulation of the Financial Sector-Review of Financial Sector Regulation and Supervision. (IMF Staff Country Reports; Country Report ;, 2004)
This paper presents an assessment of the supervision and regulation of Samoa's financial sector. The size of the offshore business remains very small compared with major offshore centers. The registration of International Business Companies represents the largest offshore business for Samoa. For offshore banks, the Samoan authorities have tightened regulatory controls following the amendment to the Offshore Banking Act in 1998, and as a result, the number of offshore banks has been reduced significantly.